Morpho-anatomical and palynotaxonomic study of the genus Onobrychis Miller (Hedysareae—Fabaceae) in Pakistan, and its systematic significance - Khan, Amjad; Sultan, Amir; Shah, Sayed Afzal; Khan, Raees; Khan, Nazar; Mumtaz, Abdul Samad; Kaleem, Muhammad; Abdullah, Muhammad; Al-Qahtani, Wahidah H.; Khan, Tahir (Phytotaxa, 2024)
The present study was designed to assess the morphology, anatomy and pollen morphology of six Onobrychis species native to Pakistan, aiming at enriching their characterization. Among the morphological features, stipules, bracts, floral segments (calyx, vexillum, wing, keel, stamen and carpel) and fruits along with seed morphology were studied. Consequently, for anatomical study slides were prepared and properly stained to assess their characters in stem, petiole, peduncle and leaflet. Among the morphological characters, the ones that significantly varied among the studied taxa were the shape and size of stipules, calyx teeth shape and size, color, shape and size of the corolla, ovary shape and size, pod along with seeds shape and size. Pollen grains were tricolpate, isopolar and radially symmetrical, prolate in shape and obtuse convex in general view. Exine ornamentation was micro-reticulate (O. cornuta and O. laxiflora), supra-reticulate (O. dealbata), micro-reticulate perforate (O. micrantha), micro-reticulate granulate (O. stewartii), and reticulate (O. tavernierifolia). Polar to equatorial ratio (P/E ratio) was measured from minimum 1.35 in O. laxiflora to maximum 1.65 in O. dealbata. In addition, ordination (PCA) and clustering (UPGMA) analysis were performed on measured pollen characters. Among the anatomical features, variations were found in the outline of the stem, petiole, peduncle and leaflet, the number of layers of collenchyma and parenchyma in the stem, number of vascular bundles, pith shape in the petiole and peduncle. In leaflets anatomy, the numbers of layers of palisade and spongy parenchyma were assessed in the studied species.